Complement-mediated inflammation and injury in brain dead organ donors. (April 2017) - Poppelaars, Felix; Seelen, Marc A.
Highlights: During brain death, both local and systemic complement is activated in the donor. Complement activation in brain death is associated with allograft function and outcome after transplantation. Complement inhibition in the BD donor reduces inflammation and injury, thus improving graft function after transplantation. Abstract: The importance of the complement system in renal ischemia-reperfusion injury and acute rejection is widely recognized, however its contribution to the pathogenesis of tissue damage in the donor remains underexposed. Brain-dead (BD) organ donors are still the primary source of organs for transplantation. Brain death is characterized by hemodynamic changes, hormonal dysregulation, and immunological activation. Recently, the complement system has been shown to be involved. In BD organ donors, complement is activated systemically and locally and is an important mediator of inflammation and graft injury. Furthermore, complement activation can be used as a clinical marker for the prediction of graft function after transplantation. Experimental models of BD have shown that inhibition of the complement cascade is a successful method to reduce inflammation and injury of donor grafts, thereby improving graft function and survival after transplantation. Consequently, complement-targeted therapeutics in BD organ donors form a new opportunity to improve organ quality for transplantation. Future studies should further elucidate the mechanism responsible for complement activation in BD organ donors.